Colectomy Rates for Ulcerative Colitis Differ between Ethnic Groups: Results from a 15-Year Nationwide Cohort Study - Ravi Misra; Alan Askari; Omar Faiz; Naila Arebi (Canadian Journal of Gastroenterology and Hepatology)
Introduction. Previous epidemiological studies suggest a higher rate of pancolonic disease in South Asians (SA) compared with White Europeans (WE). The aim of the study was to compare colectomy rates for ulcerative colitis (UC) in SA to those of WE. Methods. Patients with UC were identified from a national administrative dataset (Hospital Episode Statistics, HES) between 1997 and 2012 according to ICD-10 diagnosis code K51 for UC. The colectomy rate for each ethnic group was calculated as the proportion of patients who underwent colectomy from the total UC cases for that group. Results. Of 212,430 UC cases, 73,318 (35.3%) were coded for ethnicity. There was no significant difference in the colectomy rate between SA and WE (6.93% versus 6.90%). Indians had a significantly higher colectomy rate than WE (9.8% versus 6.9%, p<0.001). Indian patients were 21% more likely to require colectomy for UC compared with WE group (OR: 1.21, 95% CI: 1.04–1.42, and p=0.001). Conclusions. Given the limitations in coding, the colectomy rate in this cohort was higher in Indians compared to WE. A prospectively recruited ethnic cohort study will decipher whether this reflects a more aggressive phenotype or is due to other confounding factors.